Analysis of nutritional status, food consumption and socio-economic factors in preschoolers of a daycare center (Research, Society and Development, 2020)
Objective: To describe the nutritional status, food consumption and socioeconomic factors of preschoolers in a daycare center. Methodology: An observational, transversal and descriptive study of the quantitative type was carried. The sample consisted of 108 preschoolers aged 2 to 5 years. Food consumption, nutritional status and socioeconomic conditions were evaluated. For this, were applied Food Frequency Questionnaire (FFQ) and a questionnaire on socioeconomic conditions. To evaluate the nutritional status. Result: Were observed that the majority were of the brown / black race, the person in charge has complete secondary education and income of 1 to 2 minimum wages. In relation to the nutritional status, the majority were classified with eutrophic in all indices evaluated. Verified satisfactory food consumption of fruits, rice and beans. Low consumption of vegetables and moderate consumption of sweetened drinks and fast foods. Conclusion: The combination between of the three factors indicates that low income families are having access to marker food of healthy eating, which favors the good health of this group.